Historique de l’évolution des modes de financement des services de santé au Canada - Collishaw, Neil (L'Actualité économique, 1980)
AbstractThe history of Canadian government involvement in health care financing from the earliest colonial times to the present day is briefly reviewed. Particular attention is paid to the institution of major health care insurance programs and the underlying reasons for their implementation. The current financing arrangements, as dictated by the Established Programs Financing Act of 1977, are reviewed in some detail with a discussion of the advantages and disadvantages of these arrangements.